Describing work as meaningful: towards a conceptual clarification. Issue 3 (7th September 2015) - Ghadi, Mohammed Yasin; Fernando, Mario; Caputi, Peter
Abstract : Purpose: – Providing employees with meaning in their work has inspired numerous researchers to study the role of personal meaningful work and its related outcomes. Despite this high level of interest, the theoretical views and methodological approaches used to explore this concept still require refinement and development. Without a comprehensive review of these views and approaches, the concept of meaningful work will remain an ill defined notion. The purpose of this paper is to address this gap with a review of the theoretical and empirical research on meaningful work. Design/methodology/approach: – The paper includes a discussion on the concepts of "meaning" and "work", and its importance and the sources for conceptual confusion, and a synthesis of the common features that form the idea of meaningful work in numerous empirical and theoretical studies. Findings: – The paper found meaningful work is derived when the employee has a perfect understanding of the nature and expectations of the task environment (i.e. the work has a clear goal, purpose and value that is connected to the employee), the employee feels a sense of fit or congruence between their own core values and the job requirements and organizational mission and goals, and when perfect understanding exists of how employees' roles contribute to the purpose of the organization. Practical implications: – As part of an effective HRM strategy, organizations should actively encourage and develop managers' abilities to redesign jobs and the climate to build enhanced feelings of meaning in work. Furthermore, organizations can promote greater experiences of meaningful work among employees by implementing the "job crafting" concept. Also, the role of top management is to focus on job elements that would possibly change personal needs of employees and hence perceive their jobs to be more meaningful. Originality/value: – Given the limited amount of recent literature focused on defining meaningful work, this paper provides valuable resources to help organizations succeed in their understanding of how to engage in creating meaningful work environment. It also examines the underlying features that constitute the meaningful work concept and offers guidance for future research by presenting the current state of knowledge about meaningful work.